2020
DOI: 10.1021/acsinfecdis.0c00582
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Prodrug Activation by the Staphylococcal Glyoxalase GloB

Abstract: With the rising prevalence of multidrug resistance, there is an urgent need to develop novel antibiotics. Many putative antibiotics demonstrate promising in vitro potency but fail in vivo due to poor drug-like qualities (e.g., serum half-life, oral absorption, solubility, and toxicity). These drug-like properties can be modified through the addition of chemical protecting groups, creating “prodrugs” that are activated prior to target inhibition. Lipophilic prodrugging techniques, including the attachment of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…We incubated each enzyme with POM-HEX and characterized the products via 31 P- 1 H-heteronuclear single quantum coherence (HSQC) nuclear magnetic resonance (NMR). We have previously shown that GloB removes only one POM moiety, resulting in an accumulation of mono-POM-HEX (Figure 1b) 27 . Similarly, FrmB is capable of removing only one POM-moiety (Supplementary Figure 4).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…We incubated each enzyme with POM-HEX and characterized the products via 31 P- 1 H-heteronuclear single quantum coherence (HSQC) nuclear magnetic resonance (NMR). We have previously shown that GloB removes only one POM moiety, resulting in an accumulation of mono-POM-HEX (Figure 1b) 27 . Similarly, FrmB is capable of removing only one POM-moiety (Supplementary Figure 4).…”
Section: Resultsmentioning
confidence: 85%
“…In the zoonotic staphylococcal species S. schleiferi and S. pseudintermedius , loss of the enzyme GloB, a hydroxyacylglutathione hydrolase, or glyoxalase II enzyme, confers resistance to carboxy ester prodrugs because carboxy ester prodrugs are not activated 27 . However, purified GloB alone is insufficient to activate carboxy ester prodrugs in vitro , suggesting that at least one additional cellular enzyme is required.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations